Glycolytic modulations and antioxidant capacity in Amazonian fish, Bryconops giacopinii (Characiformes: Iguanodectidae), living at high temperature - de Campos, Derek Felipe [UNESP]; Mota, Susana Braz; de Almeida-Val, Vera Maria Fonseca; Val, Adalberto Luis (FapUNIFESP (SciELO), 2024)
Temperature is projected to continue increasing in the upcoming years. The effects of temperature warming in deforested stream populations have not been addressed yet and are a promising area to understand the consequences of increased temperature on fish physiology. Therefore, the aims of this study were to determine the manner in which Bryconops giacopinii from deforested habitat modulates the LDH kinetics in response to warming and whether the antioxidant system is able to withstand thermal stress. We collected individuals from two roadside streams (deforested) and one forested stream and measured the LDH kinetics parameters (Vmax and Km) for pyruvate and lactate, measured the total ROS production, and measured the activity of antioxidant enzymes and the oxidative stress biomarker. Our results showed lower affinity and higher LDH activity for lactate oxidation in road-side populations, suggesting that populations living in high temperatures use lactate as aerobic fuel. Besides, there was an increase in ROS production, and CAT and GSH levels in road-side populations, but not LPO levels, suggesting that B. giacopinni is able to neutralize the ROS production with the antioxidant systems. Our results bring important findings in the adaptation of this specie to a warm environment.
Keywords: Aclimatization; Antioxidant enzymes; Lactate dehydrogenase; Oxidative stress; Thermal adaptation